Impact of Diabetes Mellitus on Oral Cavity - Ionela Roxana Vasluianu; Alice Murariu; Magda Ecaterina Antohe; Consuela Norina Forna; Doriana Forna (Romanian Society of Oral Rehabilitation, 2012)
Introduction The pathology from the level of the oral cavity may represents sings of homeostasic disequilibrium or structural modifications on the level of the entire organism. The oral manifestations can be indicators in order to establish an early diagnosis for the general disease. Material and methods The patients suffering from diabetes mellitus were examined and they presented different pathological aspects both on general level and of the oral cavity. Within the evaluation, there were included the people that showed pain determined by dental decay, with pulp and periodontal complications, with acute periodontal inflammatory phenomena, masticatory and aesthetic dysfunctions, tension and gingival itching. For each patient, we took into account the type of diabetes, the values of the glycaemia and the followed treatment. Results In the case of the affections, on the level of the mucosa, we found lesions on the level of the tongue, marginal periodontal and labial mucosa and the edentulous ridge. Diabetes mellitus is a risk factor for the modifications on the level of the oral cavity because the patients suffering from diabetes have affections characterized by seriousness and rapid evolution. Conclusions Even if there are several general affections that can influence or accelerate the edentation, the diabetes greatly influences both the rate of the loss of odonto - parodontal units and the deterioration of the edentulous prosthetic area.